Jubal Sackett [compact disc, unabridged] - L'Amour, Louis, 1908-1988 (L'Amour, Louis, 1908-1988. Sacketts., 2000)
Wilderness explorer Jubal Sackett was the son of Barnabas Sackett, the first of that line to come to the New World. Jubal feared no man, nor did he back away from any challenge. His determination to blaze new trails took him across the vast savage North American continent where no white man had been before. Living and fighting among the Indian tribes, Jubal forged a legend as a powerful medicine man whom they called "Ni'kwana, master of mysteries." And with Itchakomi, the proud Natchez princess, he set an example of courage that future Sacketts would follow.